the effect of social media marketing on consumers in the case of small and medium enterprises - AGGARWAL, GRISHA (2017)
Purpose: The main purpose of the research is to examine the effect of social media marketing on consumers in the case of small and medium enterprises. Along with this, the research work aims to determine the advantages of social media marketing tactics over traditional means of marketing. Further, the research focuses on conducting a comparative evaluation of the effectiveness of Facebook and Youtube in attracting and engaging with consumers in the contemporary business scenario. Design/methodology/approach: The undertaken work has employed qualitative research methods for gaining a deep understanding of the research subject and investigating the research phenomenon by the use of a wide array of information as well as multiple interpretations. In order to accomplish research objectives, interpretivism research paradigm, exploratory research design and inductive approach have been applied in the current work. Primary qualitative data is collected from 20 consumers in the UK by semi-structured interview method to understand their perspectives regarding the impact of social media marketing tactics on their buying decisions. Secondary data is acquired from relevant literary sources such as scholarly articles and books. Purposive sampling technique has been used for selecting a sample from the target population, and thematic analysis technique is employed for assessing gathered data and deriving data findings. Findings: It has been found from data findings and analysis that social media marketing significantly influences consumer buying behavior due to increasing popularity of social networking sites among users. In the context of SMEs, it is identified that use of social media platforms for marketing and promoting products is regarded to be a beneficial way to attract and engage consumers in a cost effective manner. It has been found that social media platforms provide several benefits to SMEs and customers, wherein both Facebook and Youtube are regarded to be equally effective in terms of engaging consumers and influencing their buying decisions. Research implications: The research provides a comparative evaluation of two major social networking sites namely Facebook and Youtube in terms of their effectiveness in attracting consumers. Other than this, the research includes a detailed evaluation of marketing strategies employed by SMEs in the light of academic theories along with presenting a detailed analysis of benefits of social media marketing tactics and traditional marketing approaches in enticing consumers. The research has added to the data base of social media marketing management and provided vital results in regard to finding the usefulness of social networking sites in influencing consumers. Practical implications: The research has presented the main benefits of social media marketing strategies for SMEs in influencing consumer buying behavior that will be beneficial to all the small and medium enterprises in boosting their growth and profitability. In addition to this, the research consists of varied managerial recommendations that can be incorporated by SMEs for maximizing the benefits from the use of social media platforms along with suggesting consumers make effective use of social media platforms to improve their buying decisions. Limitations The research provides generalized findings in the form of theoretical and descriptive information due to use of inductive approach and qualitative data collection tools. The research does not encompass any statistical or numerical information that poses a question to the credibility and accuracy of the research outcomes.